2004
DOI: 10.2144/04372rr01
|View full text |Cite
|
Sign up to set email alerts
|

Potential influence of the first PCR cycles in real-time comparative gene quantifications

Abstract: There is an underlying assumption in real-time PCR that the amplification efficiency is equal from the first cycles until a signal can be detected. In this study, we evaluated this assumption by analyzing genes with known gene copy number using real-time PCR comparative gene quantifications. Listeria monocytogenes has six 23S rRNA gene copies and one copy of the hlyA gene. We determined 23S rRNA gene copy numbers between 0.9 and 1.6 relative to hlyA when applying the comparative gene quantification approach. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…PCR products of varying length are created during initial stages of the PCR and these products only influence reaction kinetics during the first few cycles [20]. Our work implies that template quality also impacts PCR efficiency only during these stages [21].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…PCR products of varying length are created during initial stages of the PCR and these products only influence reaction kinetics during the first few cycles [20]. Our work implies that template quality also impacts PCR efficiency only during these stages [21].…”
Section: Discussionmentioning
confidence: 80%
“…Nogva and Rudi observed that the Listeria monocytogenes 23S rRNA gene amplifies less efficiently than its hlyA gene and that restriction enzyme digests of input genomic DNA improve the amplification efficiencies of both genes. They concluded that amplification efficiency during early PCR cycles is less than the efficiency during the exponential phase [20]. Work in our lab adds template quality as a factor that impacts early cycle reaction efficiency [21].…”
Section: Introductionmentioning
confidence: 95%
“…4). It has been reported that qPCR quantification bias between 2 genes (linear DNA) originated from the amplification efficiency of first PCR cycle [6]. In the theoretical model proposed by Nogva and Rudi [6], 3 types of amplification were occurring during the PCR process (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…With our nested PCR assay, the first round of amplification with panfungal primers enriches the fungal DNA fraction and improves the fungal versus nonfungal DNA ratio. Specific oligonucleotides used in the second round can therefore easily find their targets, allowing for more-efficient PCRs (19). The preamplification step enables the detection of very low copy numbers in blood samples.…”
Section: Discussionmentioning
confidence: 99%